Treatment of pediatric high‐grade central nervous system tumors with high‐dose methotrexate in combination with multiagent chemotherapy: A single‐institution experience. Issue 3 (18th December 2019) - Bernstock, Joshua D.; Alva, Elizabeth; Cohen, Joshua L.; Lobbous, Mina; Chagoya, Gustavo; Elsayed, Galal A.; Orr, Brent A.; Rozzelle, Curtis; Rocque, Brandon; Blount, Jeffrey; Johnston, James M.; Li, Rong; et al.
Abstract: Background: Effective treatment for pediatric embryonal brain tumors includes dose‐intensive multiagent chemotherapy (DIMAC) followed by high‐dose chemotherapy with stem cell rescue (HDCSCR). Use of repeated cycles of DIMAC including high‐dose methotrexate (HDMTX) without HDCSCR has not been described. Procedure: We retrospectively reviewed the responses/toxicities in 13 patients (aged 2‐155 months, median 22 months) with central nervous system (CNS) tumors (atypical teratoid rhabdoid tumors, CNS embryonal tumors not otherwise specified, pineoblastoma, embryonal tumor with multilayered rosettes, and CNS sarcoma) treated over a 12‐year period with repeated cycles of HDMTX followed by etoposide, cisplatin, cyclophosphamide, and vincristine. Results: Six patients (46.2%) had disseminated disease at presentation and five (38.5%) had gross total resection. A total of 64 courses of therapy were administered with a median of five courses per patient. Eight patients (61.5%) received radiation therapy (one at relapse). By completion of therapy, 11 patients (84.6%) achieved a response (six complete, five partial). Six of the 13 patients (46.2%) remain alive with a median follow‐up of 48 months (6‐146). Acute toxicities included fever/neutropenia (70.3%), bacteremia (15.6%), and grade 3 mucositis (18.8%). Long‐term complications included learning disability, seizure disorder, and brain necrosis, without treatment‐related deaths. Conclusions: DIMAC with HDMTX without HDCSCR may be an effective treatment option for selected patients with embryonal or high‐grade CNS tumors.